Produzioni locali, importazioni e esportazioni dall’attuale Canton Ticino (Svizzera) - De Micheli Schulthess, Christiane (Rei Cretariae Romanae Fautorum Acta, 2022)
The initial contact between Canton Ticino and the Roman world happened at the end of the 2nd century BC, evidenced by limited imports from Central Italy. The Canton Ticino is Romanized during the Augustan period, but imports decrease as local craftspeople imitate black slip vessels, Arretine sigillata, thin walled pottery, and glass vessels. During the 1st and 2nd centuries AD Arretine sigillata is replaced by Padana and Tardo Padana, and thin walled cups in grey fabrics clearly outnumber cups in light fabrics. During the 1st century AD flanged flagons, dotted beakers, and Padana or Tardo Padana vessels of form Drag. 37/32, are confined to the region between the rivers Sesia, Ticino, Po, and Adda. Starting from the end of the 2nd century AD grave goods reveal contact with the regions north of the Alps. Gaulish sigillata vessels and Mesocco-type brooches are found in the cemeteries of Northern Ticino, whereas glass imports from the Rhenish regions, or their local imitations, occur in the cemeteries close to lake Verbano. Glazed flagons and two-handled jars replace coarse vessels in the graves, and their distribution seems to be limited to the 'Comprensorio del Ticino'.